Examining the Relationship Between Healthcare Workers' Interpersonal Relationship Styles and Social-Emotional Competence Levels and Their Exposure to Violence. - UYGUN AYKANAT, Tuğba; BAYSAN ARABACI, Leyla (Fenerbahce University Journal of Health Sciences (FBU-JOSH) / Fenerbahçe Üniversitesi Sağlık Bilimleri Dergisi, 2025)
The study was conducted to examine the relationship between the interpersonal relationship styles and social-emotional competence levels of healthcare workers and their exposure to violence. The descriptive study was conducted between January and December 2023. Data were collected using the Introductory Information Form, Interpersonal Relationship Dimensions Scale, and Social-Emotional Competence Scale. Student test and Pearson correlation analysis were used to evaluate the data. Logistic regression analysis was performed with the backward method to predict the exposure to violence. 75.9% of healthcare workers were female and the mean age was 35.3±9.0. 35.5% of healthcare workers stated that they had experienced violence at work during their working lives, 61.1% of whom were subjected to violence by a male patient relative, and 86.4% verbally. It has been reported that violence occurs more during the 16.01-00.00 shift, during treatment and care. It has been determined that there are differences in the exposure of healthcare workers to violence according to their interpersonal relationship styles. It has been determined that as healthcare workers' empathy, trust in others, and emotional awareness increase in interpersonal relationships, their ability to adapt to different situations (adaptability) also increases. Healthcare workers with lower interpersonal relationship skills (level of trust in others and emotional awareness) are exposed to more violence.